Economic Burden Can Be the Major Determining Factor Resulting in Short-Term Intermittent and Repetitive Ustekinumab Treatment for Moderate-to-Severe Psoriasis - Choi, Chong Won (Ann Dermatol, 2018)
BACKGROUND: The continuous use of biologic agents in the treatment of psoriasis has been reported to result in successful and sustained therapeutic effects and safety. However, some patients choose intermittent and repetitive treatment. OBJECTIVE: To determine the factors for selecting intermittent and repetitive ustekinumab treatment for the management of psoriasis. METHODS: From January 2011 to October 2016, we enrolled 30 psoriasis patients who discontinued ustekinumab treatment and were followed up for psoriasis treatment. We reviewed data regarding patients' clinical characteristics and the treatment they received, and investigated the factors for selecting intermittent treatment. RESULTS: A total of 52 ustekinumab treatment periods were administered to the 30 patients. Of the 52 treatment periods, 34.6% were covered by insurance and 82.4% were discontinued after sufficient improvement had been made or at the patient's request. Further analysis comparing the first and second ustekinumab treatments revealed that the patients who used ustekinumab in second treatment were more likely to be insured. In addition, the rate of patients reaching psoriasis area and severity index (PASI)75 and PASI90 was similar between the first and subsequent ustekinumab treatments. CONCLUSION: We found that the patients who used ustekinumab intermittently were those who were satisfied with the outcome of ustekinumab treatment but could not afford the treatment. These results suggested that economic burden can be a factor for the patients' choice of short-term intermittent treatment. The expansion of insurance coverage can increase the effectiveness of, and patients' satisfaction with, the management of psoriasis.